2010
DOI: 10.1002/ejoc.200900849
|View full text |Cite
|
Sign up to set email alerts
|

Direct Arylation of Imidazo[1,2‐b]pyridazines: Microwave‐Assisted One‐Pot Suzuki Coupling/Pd‐Catalysed Arylation

Abstract: Direct intermolecular C–H arylation of 6‐chloroimidazo[1,2‐b]pyridazine in its 3‐position was achieved, and the tolerance to reaction conditions in the presence of chloro groups was investigated. Various 3‐(hetero)arylimidazo[1,2‐b]pyridazines were synthesized in good to excellent yields. This methodology was successfully applied to the synthesis of 3,6‐di‐ and 2,3,6‐trisubstituted imidazo[1,2‐b]pyridazines by a microwave‐assisted, one‐pot, two‐step Suzuki cross‐coupling/palladium‐catalysed arylation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Despite the central role played by Pd-catalysed cross-coupling reactions of organometallic compounds with organo-(pseudo)halides, both in industrial 10 11 and in academic laboratories 12 13 14 15 , the corresponding solvent-free variants have been scarcely reported. Although boron compounds have been engaged in solvent-free cross-coupling reactions, thus far the use of microwaves 16 17 , ball mill 18 19 and/or high temperatures are required ( Fig. 1a ).…”
mentioning
confidence: 99%
“…Despite the central role played by Pd-catalysed cross-coupling reactions of organometallic compounds with organo-(pseudo)halides, both in industrial 10 11 and in academic laboratories 12 13 14 15 , the corresponding solvent-free variants have been scarcely reported. Although boron compounds have been engaged in solvent-free cross-coupling reactions, thus far the use of microwaves 16 17 , ball mill 18 19 and/or high temperatures are required ( Fig. 1a ).…”
mentioning
confidence: 99%
“…We started our optimization with the investigation of the direct arylation of 5,7‐dimethyl‐2‐phenylpyrazolo[1,5‐ a ]pyrimidine ( 1 )11 with 3‐bromotoluene ( 2 ). We first applied the reaction conditions already used in our laboratory 2g. Compound 1 (1 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…El Akkaoui et al (2010) [42] have demonstrated the flexibility of a MW-assisted, one-pot, twostep SMC/Pd-catalysed arylation process for the fast preparation of a library of different polysubstituted imidazo [1,2-b]pyridazine products in good yields (69%-78%) (Scheme 12). The first arylation step was performed in toluene/EtOH from 6-chloroimidazo [1,2-b]pyridazine in the presence of Pd acetate (0.1 equiv.…”
Section: Scheme 11 Mw-assisted Reaction Of Various Boronic Acids Andmentioning
confidence: 99%